Política educacional no Baixo Tocantins: a organização do ensino no município de Igarapé-Miri-PA - MORAES, Elze Cristina Brandão de Freitas (2019)
The objective of this paper is to bring results on the research project "Education Policy in the lower Tocantins: the organization of education in the municipality of Igarapé-Miri/PA". The research aims to understand how is structured the organization of education in Igarapé-Miri/PA and realize that form the social and political linkages has been debating around a proposal effectively democratic republic of ordination to the educational system in the municipality tocantinense. As methodological options were used bibliographical research and field, as well as analysis of laws and decrees used to organize the educational system. As theoretical framework of the research were used in the studies based on the literature by authors such as Libâneo (2012), Souza (2015), Meksenas (2005), as well as publications of articles and papers of completion of course on the organization of teaching through the historic process of Brazil. The field research was carried out at the Municipal Secretary of Education - SEMED municipality of Igarapé-Miri, where they were collected support materials and through informal conversations involving the Secretary of Education, members of the councils and staff members of the secretariat. The results indicate the Inconstancy in the political scene and that their unsuccessful sites has not provided with satisfaction the success of education intended by the municipalization process after the Brazilian Federal Constitution of 1988 and the Law of Guidelines and Bases of Education - LDB 9394/96. This constant the municipality presents obstacles for the organization of education systems, especially in the political question, because this whole situation creates obstacles in the consolidation of the organization, to understand that education systems are fastened through bureaucratic processes.